Chemical diversity and ontogeny of Piper species - Guerrero-Perilla, Andres Camilo (2021)
Piper (Piperaceae) is a genus of economic and medicinal importance, with over 1000 species, having the highest species diversity among the basal angiosperms. However, a considerable number of species have not been studied despite their widespread and traditional uses. In the case of P. auritum, a comprehensive phytochemical analysis was conducted for adults and plants at early stages. Leaves, fruits and roots were extracted, and the major metabolites were identified by spectrometric and spectroscopic methods. C-glycosylflavonoids, phenylbutenolides, amides and phenylpropanoids were the main sets of compounds in the species. After chromatographic profiling using HPLC-UV-HRESI, a comparison between adults (leaves, root and fruit) and seedlings (leaves) showed the rise of Cglycosylflavonoids and amide pellitorine during the early stage of ontogeny as well as the lack of phenylbutenolides and other amides, suggesting that the chemistry of the early stages corresponds to a hybrid between young leaves and roots. The species P. lindbergii and P. chimonantifolium were also studied; several metabolites like dihydrochalcones myrigalone H, dihydroflavokawain C and asebogenin, as well as chalcone stercurensin, were identified by HPLC-ESI-HRMS and NMR (1D and 2D). Several other chalcone-type metabolites were annotated for both species, suggesting them as promising sources of chalcone-type metabolites. Additionally, seven species of Piper (P. umbellatum, P. glabratum, P. diospyrifolium, P. caldense, P. regnellii, P. crassinervium (IQ and Colombia) and P. chimonantifolium were planted. Six-month-old seedlings were collected, extracted, and their HPLC and 1H NMR profiles were compared with the adults by multivariate analysis and through the differences in their composition. Two methodologies were used: individuals of P. umbellatum, P. glabratum and P. diospyrifolium; and pooled P. caldense, P. regnellii, P. crassinervium (IQ and Colombia) and P. chimonantifolium. Multivariate analysis displayed visible differences between species and phenological stage, especially for the pooled species with better clustering while individuals showed a high dispersion. HPLC results were also superior to NMR, showing the strong effect of interferents and extraction procedure in the latter. P. glabratum was compared using both methodologies, with the PCA discriminating the individual, pooled and adult samples in a better way for HPLC data. HPLC-ESIHRMS annotations showed that C-glycosylflavonoids are conspicuous in all species, adult and seedlings, while the adults become more variated, producing lignoids, chalcones, dihydrochalcones, prenylated benzoic acids and quinones. Finally, due to the ubiquitous occurrence of aristolactams in the studied species, an HPLC-FLD methodology was developed and validated to quantify the total amount of these compounds in EtOAc extracts from roots of eighteen species of Piper. During the standard cepharanone B isolation, piperolactams A-C and aristolactam DIII were identified. P. aduncum, P. aleyreanum, P. hispidum, P. cubataonum and P. krukoffi displayed the highest content of these compounds. The method was highly selective and sensitive for this study and also demonstrated high ruggedness. In general, the data obtained demonstrated the presence of compounds such as glycosylated flavonoids and aristolactams as ubiquitous in Piper species and that plant studies along ontogeny could contribute to the discovery of new secondary metabolites.